2018
DOI: 10.1080/02699052.2018.1483529
|View full text |Cite
|
Sign up to set email alerts
|

Is balance performance reduced after mild traumatic brain injury?: Interim analysis from chronic effects of neurotrauma consortium (CENC) multi-centre study

Abstract: These findings show that repeated mTBI, partially mediated by pain, may lead to later balance disturbances among military combatants. Further study of CDP outcomes within this accruing cohort is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The relationship between concussion and lower extremity injury has been extensively studied in the sports medicine literature, 10 , 15 , 16 with a number of hypotheses for the underlying mechanism, including resultant deficiencies in dynamic balance, neuromuscular control, cognitive accuracy, and gait performance. 4 , 14 , 27 , 31 , 40 This observation is corroborated by our study, which identified a concussion history as a significant risk factor in both the multivariate logistic regression and the machine learning models. Finally, an interesting protective correlation was identified between 3-point attempt rate and risk of lower extremity injury.…”
Section: Discussionsupporting
confidence: 84%
“…The relationship between concussion and lower extremity injury has been extensively studied in the sports medicine literature, 10 , 15 , 16 with a number of hypotheses for the underlying mechanism, including resultant deficiencies in dynamic balance, neuromuscular control, cognitive accuracy, and gait performance. 4 , 14 , 27 , 31 , 40 This observation is corroborated by our study, which identified a concussion history as a significant risk factor in both the multivariate logistic regression and the machine learning models. Finally, an interesting protective correlation was identified between 3-point attempt rate and risk of lower extremity injury.…”
Section: Discussionsupporting
confidence: 84%
“…Worsened visuomotor integration (by Trail Making Test TMT-B) has been reported in Service members and Veterans with mTBI (24). A separate study, using the Sensory Organization Test, reported chronic development of balance deficits and projected more frequent or severe deficits in Veterans with repetitive mTBI, as compared to those with single mTBI exposure (79). Some preclinical studies using the staircase test and neurological severity score failed to find motor deficits after LIB-induced mTBI (52,80).…”
Section: Motor Functionsmentioning
confidence: 99%
“…Multiple cohort and case-control studies and systematic reviews of moderate-quality evidence found potential motor function impairments that may be present after a concussive event, including impairments in static and dynamic balance, dual-task/multitasking gait activities, and motor coordination with complex movement tasks, which may or may not correlate with symptom reports. 11,13,20,21,44,49,58,59,68,86,89,90,[93][94][95]100,144,154,183,190,195,218,221,223…”
Section: IIImentioning
confidence: 99%
“…Multiple case series and retrospective analyses indicate that subtle, subclinical motor function impairments (eg, postural control/sway metrics or sensory integration ability) may persist beyond the presence of easily observable and detectable impairments (eg, balance tests). 28,180,200,207,221…”
Section: IVmentioning
confidence: 99%